Evaluation of knowledge, halal quality assurance practices and commitment among food industries in Malaysia - Baharudin Othman; Sharifudin Md. Shaarani; Arsiah Hj Bahron (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of this paper is to assess the level of knowledge, halal dietary quality assurance practices, and commitment among food industries in the implementation of halal in Malaysia. Besides, the study was based on two categories that are considered major contributors in the chain of halal food sector in Malaysia which are the multinational, and small medium enterprise (SME).